Análise da expressão gênica em resposta ao tratamento com Euphorbia tirucalli (Aveloz) em carcinoma epidermóide de laringe - Franco, Gabriela Bueno [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The larynx squamous cell carcinoma is the most common to hit the head and neck, representing about 25% of malignant tumors that affect this area and 2% of all malignancies. Therapeutic resources used are surgery, chemotherapy and radiation therapies, but are considered highly invasive. Therefore, some plants had been used in the treatment of cancer, in an attempt to soften the damage caused by conventional methods. One of these has attracted scientific interest, the Euphorbia tirucalli, known popularly as aveloz. This plant is used in the treatment of asthma, ulcers, warts and has active principles with activities scientifically proven as antimutagenic, anti-inflammatory and anticancer. Due of the importance the antitumoral fraction of the latex the E. tirucalli, the present study aimed to evaluate the influence of herbal of the larynx squamous cell carcinoma (Hep-2), on the morphology, cell proliferation and gene expression. The Hep-2 cells were cultured in complete medium (MEM 10%), and treated in the following concentrations of the aveloz (0,25; 2,5; 25 e 250 μg/mL) to evaluate the possible effects of this plant in 1, 3, 5 and 7 days. After statistical analysis of the test cell proliferation, was made a new culture for RNA extraction and realization of the Rapid Subtractive Hybridization technique (RaSH). The genes with altered expression, found in RaSH technique, were analyzed databases Gene Ontology (GO) and Ingenuity Systems© (IPA). The validation of the five differentially expressed genes found was performed by real time quantitative PCR. The aveloz treatment did not change the cell morphology compared with control samples and decreased the cell growth, with results more statistically significant on day 3 at a concentration of 25 μg/mL. Therefore, these parameters were chosen to continue with the methods. The RaSH approach detected change in expression of some genes, including ANXA1, TCEA1, NGFRAP1, ITPR1 and CD55, which are ...

O carcinoma epidermóide de laringe é um dos mais comuns a atingir a região da cabeça e pescoço, representando cerca de 25% dos tumores malignos que acometem essa área e 2% de todas as doenças malignas. Os recursos terapêuticos utilizados são as cirurgias, terapias por irradiação e quimioterapia, porém são considerados altamente invasivos. Por isso, algumas plantas vêm sendo utilizadas no tratamento do câncer, na tentativa de amenizar os danos causados pelos métodos convencionais. Uma dessas tem despertado interesse científico, a Euphorbia tirucalli, conhecida popularmente como aveloz. Essa planta é utilizada no tratamento de asma, úlceras, verrugas e possui princípios ativos com atividades biológicas comprovadas cientificamente como, antimutagênica, anti-inflamatória e anticancerígena. Em função da importância da fração antitumoral do látex da E. tirucalli, o presente trabalho teve como objetivo avaliar a influência desse fitoterápico nas células de carcinoma epidermóide de laringe (Hep-2), sobre a morfologia, proliferação celular e expressão gênica. As células Hep-2 foram cultivadas em meio completo (MEM 10%), e tratadas nas seguintes concentrações do aveloz (0,25; 2,5; 25 e 250 μg/mL), para avaliar o possível efeito dessa planta nos tempos de 1, 3, 5 e 7 dias. Após análises estatísticas do teste de proliferação celular, foi efetuado um novo cultivo para extração do RNA e realização da técnica de Hibridização Subtrativa Rápida (RaSH). Os genes com expressão alterada, encontrados na técnica de RaSH, foram analisados por bancos de dados Gene Ontology (GO) e Ingenuity Systems© (IPA). A validação de cinco genes encontrados como diferencialmente expressos foi realizada por PCR quantitativo em tempo real. Após o tratamento com o aveloz, a morfologia das células não sofreu alterações, quando comparada com amostras controles. No teste de proliferação celular, as células apresentaram ...
Keywords: Genética; Expressão gênica; Euforbia; Carcinoma de celulas escamosas; Reação em cadeia de polimerase; Laringe - Câncer; Gene expression